Qualidade da operação na cultura da cana-de-açúcar utilizando cartas de controle - Silva, Michel Aparecido Ferreira da [UNESP] (2015)
The agribusiness is an important sector for the national economy and all its activities need a management, because we need to increasingly reduce costs to try to increase our profitability and consequently have a longevity in the economy. One of the main items making up the production cost is fuel consumption, reaching 45% of the cost of agricultural equipment, and so we must worry about the factors that affect it. One of the factors that affect the efficiency of agricultural equipment can be the operating balance, tire type, tire pressure, soil type and type of previous crop. A major concern with the fuel consumption is the environmental issue, as the burning of fossil fuels is a source of gases to global warming. Considering these factors, this study aimed to evaluate the quality of the operation in the culture of sugarcane, using the fuel consumption of agricultural operations as an indicator of quality. The study used quality management techniques and statistical control charts of agricultural operations as an evaluation method. Fuel consumption were analyzed in the subsoil, in two types of harrowing (heavy and intermediate) and trailer towing as they are important operations in the cycle of the culture of sugarcane and especially in the preparation of the soil, and the operations They were considered stable, except the intermediate harrowing and that operations were considered unable to have results within specified limits